Institutional failure or market failure? - Mathur, Ike; Marcelin, Isaac (Journal of Banking & Finance, 2015)
We investigate the effect of the power of creditors, property rights protection, and institutional quality, on bank profits using a panel of 498 banks from 46 countries. Results show that better institutions and stronger property rights protection reduce bank profits, while stronger power of creditors drives up bank profits significantly. Results imply that better institutions and enhanced property rights protection lead to greater flow of credit allowing firms and investors to undertake more profitable ventures. By extension, stronger creditor rights erect steeper barriers to external finance for firms and investors. National indicators of economic freedoms may be more important to lowering the spread than strict creditor rights. Seemingly, credit markets fail when economic institutions fail or when governments intervene into these markets in ways that impede the safety and soundness of financial transactions and private contracting.